Progress in biomedical engineering during 2023 in China - Zhikai Yu; Zi-ang Song; Hang Xu; Jingjing Wang; Changming Wang; Guoguang Zhao (EngMedicine)
Objective: To investigate the advancements achieved by biomedical engineering laboratories in China during 2023. Methods: A total of 729 articles were initially selected from the SCI database and categorized by image, signal, gene, and mechanics, with categories of quartile 1 or higher. Subsequently, 52 representative articles were selected for this review. Results: The Chinese research team made significant strides in biomedical engineering in 2023, primarily in the following areas: traditional imaging technology, fluorescence labeling technology, photoacoustic imaging technology, neural interfaces and modulation, medical machinery, and medical materials. Significance: This review serves as an instructional manual for novices and an updated status report for experienced professionals. Additionally, comparing the achievements of Chinese teams with international teams may help shape future research directions in China.